Profiling of Microbial Community in Rearing Water of White Shrimp (Litopenaeus vannamei) Infected with White Feces Disease Syndrome - Karina Rahardjo; Woro Hastuti Setyantini; Muhamad Amin (Department of Aquaculture, 2023)
Shrimp farmers have reported mass mortality of white shrimp (Litopenaeus vannamei), reaching 2-3 kg/day in Gerongan Village, Kraton District, Pasuruan Regency in mid-2021. Preliminary analysis suggests that mass mortality was caused by bacterial diseases. Thus, to find out the main pathogen causing the mass mortality, the present study investigated microbial composition in rearing media of white shrimp (Litopenaeus vannamei) infected by the white feces disease (WFD) and healthy white shrimp using next-generation sequencing (NGS) technology. The research was conducted by collecting normal water samples and infected shrimp pond water samples. The results of the NGS assay showed that Vibrio vulnificus was found dominant in WFD-infected shrimp pond water, therefore was suspected to be the main cause of WFD.